Frontispiece: Diverse Ligand‐Functionalized Mixed‐Valent Hexamanganese Sandwiched Silicotungstates with Single‐Molecule Magnet Behavior. Issue 35 (12th August 2016) - Xue, Han; Zhao, Jun‐Wei; Pan, Rui; Yang, Bai‐Feng; Yang, Guo‐Yu; Liu, Hong‐Sheng
Abstract : Polyoxometalates A series of mixed‐valence Mn6 ‐sandwiched polyoxometalates (POMs) with SMM behavior have been hydrothermally made, in which the covalently functionalized Mn6 cluster via organic ligands are first observed in POMs. For more details, see the Full Paper by J.‐W. Zhao, G.‐Y. Yang, H.‐S. Liu et al. onpage 12322 ff.